2008
DOI: 10.4067/s0717-97072008000100026
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Essential Oils From Five Plant Species Against the Granary Weevils Sitophilus Zeamais and Acanthoscelides Obtectus (Coleóptera)

Abstract: Essential oils obtained from Gomortega keule, Laurelia sempervirens, Origanum vulgare, Eucalyptus globulus, and Thymus vulgaris were analyzed by gas chromatography and gas chromatography-mass spectrometry and evaluated for their toxicity against adults of Sitophilus zeamais (Motschulky) and Acanthoscelides obtectus (Say) (Coleoptera). Contact toxicity was assayed by impregnating filter paper discs with the oils. The amount of essential oils applied in each desiccator (4 l capacity) was 4, 8, 16, or 32 µl, corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
22
2
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 7 publications
(8 reference statements)
6
22
2
8
Order By: Relevance
“…Ascaridole, as one of the most abundant components agrees with the results of Bittner et al (2008) and Niemeyer and Teillier (2007) who documented concentrations as high as 38.9% and 60.3%, respectively. However, Urzúa et al (2010) considered that 1,8-cineole was the main component (36.62%) of P. boldus.…”
Section: Phytochemical Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…Ascaridole, as one of the most abundant components agrees with the results of Bittner et al (2008) and Niemeyer and Teillier (2007) who documented concentrations as high as 38.9% and 60.3%, respectively. However, Urzúa et al (2010) considered that 1,8-cineole was the main component (36.62%) of P. boldus.…”
Section: Phytochemical Analysissupporting
confidence: 91%
“…For example, Urzúa et al (2010) found insecticidal properties of P. boldus essential oil against Musca domestica L. and Bittner et al (2008) and Betancur et al (2010) indicated that this oil showed insecticidal activity against S. zeamais and Acanthoscelides obtectus. But the Monimiaceae family has other two native plants from Chile, Laurelia sempervirens (Ruiz & Pav.)…”
Section: Introductionmentioning
confidence: 99%
“…Los mejores resultados de control se han obtenido con plantas aromáticas, en especial de la familia Monimiaceae (Bittner et al, 2008). En Chile, esta familia tiene solo tres especies nativas: Peumus boldus Molina (boldo), Laurelia sempervirens (Ruiz et Pau.)…”
unclassified
“…Tul (laurel) y Laureliopsis philippiana Looser (tepa) (Rodríguez et al, 2005). Bittner et al (2008) y Betancur et al (2010) describieron el efecto insecticida de contacto y fumigante además de actividad repelente del aceite esencial de P. boldus contra S. zeamais y Acanthoscelides obtectus (Say) (Bruchidae). Bittner et al (2008) y Zapata y Smagghe (2010), encontraron que el aceite esencial de L. sempervirens presenta efecto insecticida fumigante sobre A. obtectus, y Tribolium castaneum (Herbst) (Tenebrionidae).…”
unclassified
See 1 more Smart Citation